Correction: “The Nordic Region: Can Russia Divide and Rule? Four Russo-Nordic Relations After Crimea and Trump”, (2019, Vol. 14, No. 2, pp. 101−128) - Ejdus, Filip; Džuverović, Nemanja (Journal of Regional Security, 2020)
Due to the error in the transmission of files in the layout process, a different version of the text had been published from the present one that was provided by the author and approved by the Editors. The Editors would like to apologize for this technical mistake to the author and to the readers. We acknowledge that the version that the author sent to the Journal of 14 September is the correct one, and that there are the following minor revisions that need to be made to the version of the article that had been firstly published in Journal of Regional Security Vol. 14, No. 2. The list of corrections shall be published in Journal of Regional Security Vol. 15, No. 1 both, in print and online. The corrected article shall be published online, replacing the previously published within Vol. 14, No. 2 in print and online.